Epigenetics and Chromatin - Jeanteur, Philippe.; Jeanteur, Philippe. (Progress in Molecular and Subcellular Biology, 2005)
Epigenetics refers to heritable patterns of gene expression which do not depend on alterations of genomic DNA sequence. This book provides a state-of-the-art account of a few selected hot spots by scientists at the edge in this extremely active field. It puts special emphasis on two main streams of research. One is the role of post-translational modifications of proteins, mostly histones, on chromatin structure and accessibility. The other one deals with parental genomic imprinting, a process which allows to express a few selected genes from only one of the parental allele while extinguishing the other.